Vitamin A and Its Multi-Effects on Pancreas: Recent Advances and Prospects - Zhou, Yunting; Wang, Huiying; Zhou, Junming; Qiu, Shanhu; Cai, Tingting; Li, Huiqin; Shen, Ziyang; Hu, Yun; Ding, Bo; Luo, Menghui; Huang, Rong; Yan, Rengna; et al. (Frontiers in Endocrinology, 2021)
Vitamin A(VA), which is stored in several forms in most tissues, is required to maintain metabolite homeostasisand other processes, including the visual cycle, energy balance, epithelial cell integrity, and infection resistance. In recent years, VAmolecules, also known as retinoids, have been extensively explored andused in the treatment ofskin disorders and immune-related tumors. To date, several observational and interventional studies have explored the relationship betweenVA status and the pathogenesis ofdiabetes.In particular, VAmicronutrientshave been shown toregulatepancreatic development,β-cellfunction, pancreatic innate immuneresponses, and pancreatic stellate cells phenotypesthrough multiple mechanisms.However, there are still many problems to be proven or resolved. In this review, we summarize and discuss recent and available evidence on VA biologicalmetabolism inthe pancreas. Analysis of the effects of VA on metabolism in the pancreas will contribute to our understanding ofthesupportive physiological roles of VA in pancreasprotection.